Digital SignageSistem Antrean PembayaranUang Kuliah Tunggal (Ukt) MahasiswaPoliteknik Negeri Tanah Laut - Romadhona, Meta Nuarida; Fathurrahmani, Fathurrahmani (Universitas Nusantara PGRI Kediri, 2019)
Queue is part of a service process commonly encountered in activities, such as a queue in front of the counter to make a single tuition payment (UKT) for students. At the state Polytechnic of Tanah Laut, the queue of students who want to pay for UKT in each semester is often irregular. This is because the lack of awareness of students in implementing the queuing culture and the absence of sequence number queue. In addition to the queue sequence number, the delivery of information about queuing management also does not exist, so that need a system that can function as delivery of information in the form of Digital Signage. This system is a system that can convey information to students who want to pay UKT, information that will be delivered in the form of sequence numbers in audio (sound) and visual (picture). This system also has a feature in order to store data transactions of students who have paid UKT for data storage process is more effective because it does not have to do recording repeatedly.